PENGARUH LAJU PERTUMBUHAN EKONOMI TERHADAP PENYERAPAN TENAGA KERJA DI KABUPATEN LOMBOK BARAT - Lalu Mimbar; Muhammad Yusuf (Sekolah Tinggi Ilmu Ekonomi AMM, 2016)
This study entitled Effect of Economic Growth Rate Of Manpower Absorption in West Lombok. This research was conducted with the aim of: 1). Knowing the general description of the growth rate of the industrial sector, investment and wages on employment in Lombok Barat. 2). Analyze the effect of the growth rate of the industrial sector, investment and wages on employment in West Lombok. 3). Analyze the effect of the growth rate of the industrial sector, investments and wages simultaneously on employment in West Lombok. This study was designed with quantitative research, quantitative approach basically emphasizes the analysis of numerical data (numbers) are processed with statistical methods. With quantitative methods will be acquired significance or significance of group differences in the relationship between the variables studied. This research. aimed to describe and analyze the rate of growth of the industry sector, investment and wage employment towards industry sector in West Lombok. The results showed that the development of industrial sector growth rate during the year of observation showed a decreasing trend with an average growth of 5.42%, the growth rate of the industrial sector variables affects the industrial sector employment in West Lombok. Variable investment and significant positive effect on employment in the industrial sector of West Lombok. So that when investment rises it will be followed by the industrial sector employment in West Lombok. Variable salary positive and significant effect on employment in West Lombok. So that when wages rise, the industrial sector employment will rise. Based on the test together shows that the independent variable growth rate of the industrial sector, investments and wages simultaneously affect the labour industrial sector in West Lombok